Implementation of limited liability principles and doctrine of piercing the corporate veil in management of local liability companies - ABDUL HALIM BARKATULLAH (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aims to analyze how limited liability in the Piercing the Corporate Veil doctrine is used by BUMD administration in the form of Local Liability Companies.Methodology: The normative law method was employed in this study; this is the process of looking for the rule of law, legal principles, or legal doctrines to provide a solution to a legal problem, followed by an analysis of that problem using inductive reasoning.Findings: Due to these studies’ findings, a company is considered a separate entity from its founders, members, or investors when recognized as a legal entity under the law. Important to the company’s legitimacy is the idea of the Perseroan (company) as a separate legal entity whose assets are kept separate from those of its shareholders and for whom there is limited personal liability. Second, the current regulations on UUPT also apply to the administration of BUMDs structured as Local Liability Companies. Novelty/Implications: As a result of the limited liability of shareholders, this doctrine safeguards the interests of vulnerable outsiders.